Cross‐sectional study of pigmented lesions of the head and neck in adults aged 40 years and above. (5th December 2020) - Chiu, Frank Po‐Chao; McLaren, Dythea; Pool, Louis; Shao, Emily; De'Ambrosis, Brian; Muir, James
Abstract: The diagnosis of junctional and lentiginous naevi on sun‐damaged skin of the head and neck in adults has been questioned in the literature, with the implication that these lesions should be classified as melanoma in situ. This could result in the overdiagnosis and overtreatment of non‐malignant lesions. We conducted a cross‐sectional study of the histopathological diagnosis of pigmented lesions biopsied from the head and neck of adults ≥40 years of age that were submitted to a large, Queensland‐based pathology centre over seven months. Out of 543 lesions assessed, 293 (54.0%) were flat and 250 (46.0%) were raised. Flat naevi consisted of junctional/lentiginous and compound naevi, either with or without dysplasia. Collectively, flat naevi had a prevalence slightly less than that of melanoma (15.0% versus 19.0% among flat lesions, respectively, and 8.1% versus 11.2% among all lesions, respectively). The mean age of biopsy for all junctional/lentiginous naevi was significantly greater than that of all compound naevi (65.0 years versus 52.2 years; P  = 0.001). Junctional/lentiginous naevi were significantly more associated with the neck than intradermal naevi ( P  < 0.001). In conclusion, benign, flat naevi account for a significant proportion of head and neck lesions in adults ≥40 years of age, and their location alone should not outweigh their histopathology when reaching a diagnosis.